The Management of Psoriatic Arthritis in Italy: Organizational Impact Analysis of Optimized Pathways - Restelli, Umberto; Selmi, Carlo; Pacelli, Valeria; Croce, Davide; Costanzo, Antonio (Farmeconomia. Health Economics and Therapeutic Pathways, 2019)
BACKGROUND: The management of psoriatic arthritis requires competencies in the fields of both rheumatology and dermatology, and a multidisciplinary approach. AIM: To propose an effective pathway for the diagnosis, monitoring and treatment of psoriatic arthritis in the Italian context, and to assess its organizational impact on the Regional Health Service of Lombardy Region. METHODS: The analysis was performed through interviews conducted with two key opinion leaders in the areas of dermatology and rheumatology. The current pathway of patients who present symptoms that might be related to psoriatic arthritis was defined and an optimized pathway was then proposed on the basis of the clinical practice, considering the implementation of a dermatology and rheumatology shared outpatient service. The organizational impact of the optimized pathway was then assessed from both the hospital and that of the Regional Health Service of Lombardy Region perspectives. RESULTS: The implementation of the service would have a positive impact on patients’ experience, improving the quality of the service provided, thanks to the multidisciplinary approach adopted, limiting the patients’ resources needed for the diagnosis, reducing the number of visits and time loss. The optimized pathway, therefore, would have a limited impact on the marketing mix, while potentially improving patients satisfaction, increasing the possibility of patients’ retention. To successfully implement the dermatological and rheumatologic multidisciplinary service, a precise communication strategy is mandatory. CONCLUSIONS: The optimized pathway for the diagnosis and management of psoriatic arthritis proposed would have a limited organizational impact at both hospital and Regional Health Service levels, while leading to theoretical benefits in terms of a prompt diagnosis of the pathology.